AL-MUHASINAT AL LAFZIYYAH FI SURATI ASY-SYU’ARA (DIRASAH TAHLILIYAH BADI’IYYAH) - Hanafi Hanafi; Moh. Mahbub; Muhammad Nanang Qosim (Universitas Islam Negeri Mataram, 2025)
This research includes two issues: First, it is necessary to know these rhetorical devices, especially for Indonesian students who are learning Arabic. The second issue is that the function of the Arabic language for Muslims in understanding the meanings of the Quran is very necessary for increased faith, and therefore the researcher wanted to take Surat Ash-Shu'ara' as a model to know the verses that include the types of embellishments, and this research focuses on verbal embellishments from the science of rhetoric. Therefore, this study aims to discover the miraculous aspect of the Quran from the point of view of what Allah has endowed it with in terms of beautiful composition and skillful structures, and to uncover its rhetorical secrets through its beautiful words. The research method is using the analytical descriptive approach, which is a method based on an accurate description of phenomena, and depends on describing and explaining what exists. The study proved the presence of verbal embellishments in Surat Ash-Shu'ara', and the research results included 5 cases of alliteration, 5 cases of pauses, 1 case of tasree', 3 cases of taddeed/replacing the second half of the verse to the first half of the verse, and 1 case of tatreez.